2020
DOI: 10.3390/forecast2040024
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Semi-Empirical Dynamic Model to Forecast the Propagation of the COVID-19 Epidemics in Spain

Abstract: A semiempirical model, based in the logistic map, was developed to forecast the different phases of the COVID-19 epidemic. This paper shows the mathematical model and a proposal for its calibration. Specific results are shown for Spain. Four phases were considered: non-controlled evolution; total lock-down; partial easing of the lock-down; and a phased lock-down easing. For no control the model predicted the infection of a 25% of the Spanish population, 1 million would need intensive care and 700,000 direct de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Making a comparison with the information provided by other studies, we can see how the already refined statistics from the National Epidemiology Center (CNE) of Spain indicate that the nation-wide first-wave infection peak occurred on 20 March, 6 days after the national lockdown was implemented, and the cases of COVID-19 steadily decreased after then (see [39] for details). Other studies place the peak on 26 March (Guirao, [40]), while in the work of Mora et al [41] an interval is established that goes from 29 March to 3 April. Since the first week of July, Spain experienced an increasing trend in the cumulative incidence.…”
Section: Discussionmentioning
confidence: 90%
“…Making a comparison with the information provided by other studies, we can see how the already refined statistics from the National Epidemiology Center (CNE) of Spain indicate that the nation-wide first-wave infection peak occurred on 20 March, 6 days after the national lockdown was implemented, and the cases of COVID-19 steadily decreased after then (see [39] for details). Other studies place the peak on 26 March (Guirao, [40]), while in the work of Mora et al [41] an interval is established that goes from 29 March to 3 April. Since the first week of July, Spain experienced an increasing trend in the cumulative incidence.…”
Section: Discussionmentioning
confidence: 90%
“…It is initially developed to predict population growth (Kendall and Fox, 1998;Lloyd, 1995) and has been used widely in the ecological model (Storch et al, 2017) , cryptography (Moysis et al, 2020) , data encryption (Huang andDing, 2020;Moysis et al, 2020;Raghuvanshi et al, 2020). The application of a logistic map in the study of COVID-19 can be found in past studies (Mora et al, 2020;Koltsova et al, 2020;Pelinovsky et al, 2020). Simple mathematical structure and broad chaotic systems in Logistic map make the model widely used in many elds.…”
Section: Introductionmentioning
confidence: 99%
“…A new Bayesian indicator is introduced in [2] to forecast the beginning of a new wave. In [3], semi-empirical models based on the logistic map are considered in order to predict the variables in different phases of the pandemic in Spain. Likewise, Ref.…”
Section: Introductionmentioning
confidence: 99%